2008
DOI: 10.1111/j.1464-5491.2008.02508.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year (1996–2005) prospective study of the incidence of Type 1 diabetes in Moscow in the age group 0–14 years

Abstract: This is the first study to report on validated incidence data for T1D in Moscow. We conclude that the incidence of T1D in Moscow is comparable to that of those European countries having intermediate incidence rates, and that the incidence is increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…As expected, the incidence rate in our pediatric population was higher than that reported from China, Japan, Iran, and Venezuela, but somehow was lower than the rates reported from Saudi Arabia (27.5/105) and Kuwait (20.1/105) (4,10,18,24,25). The incidence reported from Russia for children in Moscow was higher (12.9/105) than that in our sample (26). The largest T1DM prevalence study from Turkey in the pediatric age group was conducted by Akesen et al (27) in 2009 and comprised 1630751 school-aged children (range: 6-18 years) from Istanbul.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…As expected, the incidence rate in our pediatric population was higher than that reported from China, Japan, Iran, and Venezuela, but somehow was lower than the rates reported from Saudi Arabia (27.5/105) and Kuwait (20.1/105) (4,10,18,24,25). The incidence reported from Russia for children in Moscow was higher (12.9/105) than that in our sample (26). The largest T1DM prevalence study from Turkey in the pediatric age group was conducted by Akesen et al (27) in 2009 and comprised 1630751 school-aged children (range: 6-18 years) from Istanbul.…”
Section: Discussioncontrasting
confidence: 81%
“…This ratio was higher than the DKA rates reported in cross-sectional studies (33% and 43.1%)from Turkey (38,39,43)and from European countries (12,26,44,45). It has also been reported that the rate of presentation with DKA tends to decrease over time due to increased awareness on the part of the parents (45,46,47).…”
Section: Discussioncontrasting
confidence: 65%
“…From the geographical point of view, areas beginning with moderate‐low incidences including Croatia, Lesser Poland, Moscow, Belgrade, Nile Delta of northern Egypt, Shanghai city of China, and Korea exhibit a steep escalation of their annual incidences (usually >5% per year and in Shanghai >10% per year). By contrast, stabilization after years of the upward trend has been observed since the first decade of 21st century, mainly in regions already presenting high T1D incidences such as the 3 Nordic countries described above, Ireland, Czech, Biscay, Sardinia, Saudi Arabia, and Western Australia .…”
Section: Epidemiologymentioning
confidence: 99%
“…9,31,42 In contrast to the consistently high incidence rates in Caucasians, incidences of T1D in Arabs range from as high as 40.9/100 000 in Kuwait 27 to 29.0/100 000 in Saudi Arabia 3 to slightly higher than 10/100 000 in Israel. 18 Next come countries in southeast Europe 12,35,[37][38][39] which usually manifest a moderate risk for T1D with incidences around 10/ 100 000 person-years. Last, but not least, incidences as low as 1 to 5 cases/100 000 person-years are not uncommon in Latin America, 40,43 Africa, 19,41 and Asia.…”
Section: Incidence Of T1dmentioning
confidence: 99%
See 1 more Smart Citation